Social distancing and changes in drug use: Results from a cross-sectional study during the COVID-19 pandemic in Brazil - Nin, Maurício Schüler; Heidrich, Nubia; Almeida, Felipe B.; Izolan, Lucas R.; Constant, Hilda M. R. M.; Freese, Luana; Gomez, Rosane; Barros, Helena M. T. (Frontiers in Psychiatry, 2022)
Background: The outbreak of coronavirus disease 19 has led to measures of social distancing and quarantine worldwide. This stressful period may lead to psychological problems, including changes in substance use. In addition, sociodemographic factors are linked to changed levels of drug use and abuse observed during the COVID-19 pandemic, which are also associated with increased anxiety, depression, and other disorders. Thus, the aim of the study was to investigate (i) changes in drug use during the COVID-19 pandemic associated with social distancing, and (ii) to verify factors associated with those changes. Methods: A web-based cross-sectional observational survey was completed by a self-selected adult general population in Brazil (n = 2,435) during September/October 2020 (first wave) before and throughout the pandemic. Key outcomes: social distancing, self-reported drug use (ASSIST), and emotional states (DASS-21). Results: High social distancing was associated with fewer chances (prevalence ratio) of increased drug use for alcohol (0.71, CI95%: 0.64-0.80), tobacco (0.72; CI95%: 0.60-0.87), cannabis (0.65; CI95%: 0.55-0.78), and others. Low social distancing presented a higher DASS-21 score for anxiety (P =.017). Concerning covariates analysis by a general linear model, men (alcohol: 1.71; cannabis: 3.86), younger age (alcohol: 0.97), less education (alcohol, tobacco, cannabis and cocaine/crack comparing several lower schooling categories versus higher education), lower income (alcohol: 0.42; tobacco: 0.47; and cannabis: 0.36), and higher depression DASS-21 score (alcohol: 1.05; tobacco: 1.08; cannabis: 1.07; and cocaine/crack: 1.07) were associated with higher use prevalence of several drugs. Conclusions: Individuals reporting low social distancing increased the use of most drugs during the pandemic, while high social distancing significantly decreased drug use. Anxiety and depressive states and several sociodemographic factors (men; lower income; less education) were associated with higher drug use patterns.